Respuesta :

Answer:

  [tex]v=\dfrac{h+gt^2}{t}[/tex]

Step-by-step explanation:

As with any "solve for" problem, you undo what has been done to v, in reverse order. In this equation v has been ...

  • multiplied by t
  • had gt^2 subtracted from the product

So, the first step is to undo the subtraction by adding gt^2 to the equation:

  h +gt^2 = vt

Now, we undo the multiplication by dividing by the coefficient of v.

  (h +gt^2)/t = v

Lanuel

Making v the subject of formula is [tex]v = \frac{h}{t} + gt[/tex]

In this exercise, you're required to solve for v in the mathematical (algebraic) expression by making it the subject of formula.

Given the following mathematical (algebraic) expression;

[tex]h = vt - gt^2[/tex]

We would simplify the mathematical (algebraic) expression by moving the variables with v;

[tex]vt = h + gt^2[/tex]

Next, we would divide both sides by t;

[tex]v = \frac{h + gt^2}{t}[/tex]

Simplifying further, we have;

[tex]v = \frac{h}{t} + gt[/tex]

Therefore, making v the subject of formula is [tex]v = \frac{h}{t} + gt[/tex]

Find more information: https://brainly.com/question/21866313

ACCESS MORE